Exploring the Benefits of Recreational Sports: Promoting Health, Wellness, and Community Engagement - Kurniawan, Randa; Srijaroon, Archrawadee; Mousavi, Seyed Hamd (Journal Evaluation in Education (JEE), 2022)
Purpose of the study: This research aims to determine the perception of visitors who carry out recreational sports activities at the Kota Baru sports hall, Jambi Province Methodology: This study employed a quantitative method with a descriptive design. The sample was selected using simple random sampling technique. The instrument utilized in this research was a questionnaire assessing public perception in recreational sports activities at Kota Baru Sports Hall, Jambi. Data analysis was conducted using descriptive statistics. Main Findings: The research conducted at Kota Baru Jambi sports hall reveals that public perception of recreational sports activities is predominantly positive, with 53.3% of respondents rating it as quite good. The study highlights the significance of recreational sports in promoting healthy lifestyles and social interaction. Additionally, it emphasizes the need for policy interventions to enhance facilities and diversify recreational offerings. This research contributes to understanding public perceptions and underscores the importance of recreational sports in fostering community well-being. Further investigation is recommended to explore specific factors influencing participation. Novelty/Originality of this study: The study at Kota Baru Jambi sports hall unveils public perception of recreational sports, emphasizing its positive impact on health and social interaction. It underscores the importance of policy interventions for facility enhancement and activity diversification. This research contributes to understanding community perceptions and promoting well-being through recreational sports. Further exploration of participation influencers is recommended.